(untitled) (Research, Society and Development, 2022)
This study has the objective of describing the epidemiology of dermatophilosis in cattle, horse, and sheep in the southern of Rio Grande do Sul during a period of 10 years. Data was gathered of all cases/outbreaks of dermatophilosis in ruminants and equines There were 44 (49,4%) diagnoses of dermatophilosis out of 89 cases presenting non-proliferative cutaneous lesions. Of these, 13 were in cattle, 29 in horses, and two were in sheep. It was made a consultation to the Hospital de Clínicas of Porto Alegre/RS and DATASUS database to determine the occurrence of dermatophilosis in humans due to its zoonotic characteristic. It was observed that both in public hospitals and in the SUS database, dermatopathies are recorded in a non-specific way, and with dermatophilosis being a dermatopathy with nonspecific lesions, the definitive diagnosis with the characterization of the agent is not made. The results of this study allowed to conclude that dermatophilosis has a relative importance in domestic species since mortality not occurs in cattle and horses. Still, one must consider the lower dairy production in cattle. In sheep, there was mortality and losses due to the fall in wool quality, and the disease should be considered in diagnosing skin lesions in this species. In humans, the disease is underreported and the possibility of its occurrence in rural areas is alerted; however, cases rarely reach the laboratory.